Adsorption von CO2 und racemischen Wirkstoffen an nanoskaligen Trägern1. Issue 3 (17th January 2014) - Bolten, Dennis; Staudt, Reiner; Türk, Michael; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> A new idea for the separation of racemic pharmaceuticals is presented. This process applies nanoscale AlO(OH) hollow spheres as adsorbent and supercritical CO2 (sc‐CO2) as solvent. The deposition of the racemic pharmaceuticals (RS)‐flurbiprofen, (RS)‐ibuprofen, (RS)‐ketoprofen, and their enantiomers (S)‐flurbiprofen, (S)‐ibuprofen, and (S)‐ketoprofen on AlO(OH) hollow spheres is presented and evaluated. Furthermore adsorption data of gaseous CO2 on hollow spheres and commercial AlO(OH) particles from magnetic suspension balance measurements are compared. Finally, first results from an exploratory analysis concerning the adsorption of racemic flurbiprofen on the hollow spheres are presented.